Bio-compost behaviour as soil additive by food waste pretreatment on the growth of Abelmoschus esculentus L.: a systematic review - Muruga, Miiraa; Arumugam, Veknesh; Ismail, Muhammad Heikal (Universiti Putra Malaysia Press, 2021)
Food waste (FW) has always been a significant issue faced by almost all countries worldwide. The rise in FW does not only influence one’s food supply, yet the greenhouse gas (GHG) emission such as methane (CH4) and carbon dioxide (CO2) gas leads to global warming and health issues. This paper reviews the primary FW treatments available in all countries. Most advanced countries have accomplished that the least cost and most efficient FW treatment is composting. Among all the composting methods available, vermicomposting (VC) that uses redworms (Eisenia fetida) produces nutrients rich biocompost, as proven in the existing literature. Furthermore, bio-compost produced by the VC method nourishes plant growth. In this study, the primary research data sources are 78 scientific articles over the last few years. This research is the consensus on VC as the FW treatment. Besides, briefly discuss the FW pretreatment methods, the effect of bio-compost on soil properties, and their corresponding effects on the growth of Abelmoschus esculentus L.